Addition of atezolizumab to nab-paclitaxel plus carboplatin is a new standard option for the first-line treatment for non-squamous non-small cell lung cancer - Yamaguchi, Teppei; Hida, Toyoaki (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
For over a decade, the discovery of driver oncogenes and the development of specific targeted drugs have led to significant advances in the treatment for metastatic non-small cell lung cancer (NSCLC). Molecular targeted drugs targeting EGFR, ALK, ROS1, and BRAF have been developed, and each advance has resulted in improved outcomes in NSCLC. Meanwhile, in the absence of molecular targeted drugs, patients have frequently received platinum combination therapy, which is associated with progression-free survival (PFS) and overall survival (OS) of 4–6 and 9–12 months, respectively (1,2).